EFEKTIVITAS WEBINAR EDUKASI DALAM MENINGKATKAN PENGETAHUAN GURU DI KABUPATEN BOGOR - Hasanah, Tita; Irzalinda, Vivi (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
The purpose of this research is to determine the effectiveness of webinar activities which since the Covid-19 pandemic have become increasingly popular among many groups. The research method used was Pre-Experimental with a one group pretest posttest design. The treatment provided is in the form of a webinar activity via Zoom Meeting. The population of this research is Early Childhood Education (PAUD) teachers in Pamijahan District, Bogor Regency. The research sample was taken using a quota sampling technique of 30 people who met certain criteria. The primary data is in the form of test results given before and after the webinar activity given to the sample. The research analysis is descriptive and inferential analysis using Paired Samples T-Test. The results of the paired difference test show that there is a significance value of p=0.000 (p<0.05), meaning that there is a significant difference between before and after treatment. This shows that there was an increase in knowledge after the teachers participated in the webinar activities.